Organic Sonosensitizers for Sonodynamic Therapy: From Small Molecules and Nanoparticles toward Clinical Development. Issue 42 (4th August 2021) - Li, Dong; Yang, Yang; Li, Dengfeng; Pan, Jie; Chu, Chengchao; Liu, Gang
Abstract: Sonodynamic therapy (SDT) is a novel noninvasive therapeutic modality that combines low‐intensity ultrasound and sonosensitizers. Versus photo‐mediated therapy, SDT has the advantages of deeper tissue penetration, high accuracy, and less side effects. Sonosensitizers are critical for therapeutic efficacy during SDT and organic sonosensitizers are important because of their clear structure, easy monitoring, evaluation of drug metabolism, and clinical transformation. Notably, nanotechnology can be used in the field of sonosensitizers and SDT to overcome the inherent obstacles and achieve sustainable innovation. This review introduces organic small molecule sonosensitizers, nano organic sonosensitizers, and their clinical translation by providing ideas and references for the design of sonosensitizers and SDT so as to promote its transformation to clinical applications in the future. Abstract : Sonosensitizers play an important role in sonodynamic therapy (SDT). Organic small molecule sonosensitizers have been widely used in SDT because of their high sonosensitive activity and clear structure, and some porphyrins have been used in clinical sonodynamic anti‐tumor or anti‐atherosclerosis. In addition, organic nanosonosensitizers are proposed to improve the efficiency of small molecule sonosensitizers and expand their functions.